The Development of a Viral Mediated CRISPR/Cas9 System with Doxycycline Dependent gRNA Expression for Inducible In vitro and In vivo Genome Editing - de Solis, Christopher A.; Ho, Anthony; Holehonnur, Roopashri; Ploski, Jonathan E. (Frontiers in Molecular Neuroscience, 2016)
The RNA-guided Cas9 nuclease, from the type II prokaryotic Clustered Regularly Interspersed Short Palindromic Repeats (CRISPR) adaptive immune system, has been adapted and utilized by scientists to edit the genomes of eukaryotic cells. Here, we report the development of a viral mediated CRISPR/Cas9 system that can be rendered inducible utilizing doxycycline (Dox) and can be delivered to cells in vitro and in vivo utilizing adeno-associated virus (AAV). Specifically, we developed an inducible gRNA (gRNAi) AAV vector that is designed to express the gRNA from a H1/TO promoter. This AAV vector is also designed to express the Tet repressor (TetR) to regulate the expression of the gRNAi in a Dox dependent manner. We show that H1/TO promoters of varying length and a U6/TO promoter can edit DNA with similar efficiency in vitro, in a Dox dependent manner. We also demonstrate that our inducible gRNAi vector can be used to edit the genomes of neurons in vivo within the mouse brain in a Dox dependent manner. Genome editing can be induced in vivo with this system by supplying animals Dox containing food for as little as one day. This system might be cross compatible with many existing S. pyogenes Cas9 systems (i.e. Cas9 mouse, CRISPRi, etc.), and therefore it likely can be used to render these systems inducible as well.